Testing the Causal Model of the Mediating Role of Teacher Motivation in the Relationship between New Teachers' Self-Efficacy and Occupational Commitment by the Recruitment Method - monire salehi; fatemeh sahraei sarmazdeh (Allameh Tabataba'i University Press, 2022)
The aim of the present study was to investigate the causal relationship between teacher motivation and self-efficacy with new teachers' professional commitment through a causal model based on Bandura's cognitive-social theory and self-determination theory. Quantitative research method is descriptive and structural equations. The newly-employed teachers of Khorasan Razavi starting to work in 1995, 1996 and 1997, constitute the statistical population of the research. In order to test the model, a sample of 347 subjects was selected from 3339 newly-employed teachers in Khorasan Razavi. Questionnaires of teacher motivation, teacher self-efficacy and teacher professional commitment were developed and validated by the researcher. Pearson correlation coefficient, confirmatory and exploratory factor analysis, t-test and structural equation model were used to analyze the data. The results of Pearson correlation showed that teacher motivation, teacher self-efficacy and teacher professional commitment were correlated with each other (p < 0.05). By implementing the structural equation model to test the relationship between teacher motivation and teacher self-efficacy and professional commitment, it was found that the proposed model has a good fit and professional commitment is well predicted and explained through teacher self-efficacy and teacher motivation as: NNFI = 0.93, RSMEA = 0.09.